A Facile Route to Thin Films of Zinc Carbodiimide Using Aerosol‐assisted CVD. Issue 10 (10th November 2015) - Kaye, Karl M.; Grantham, William; Hyett, Geoffrey
Abstract : There has been a resurgence of interest in metal carbodiimides in recent years and in this paper we present a route to the synthesis of one of these phases, zinc carbodiimide, previously known as zinc cyanamide, in the form of a sub‐micrometer thin film, using aerosol‐assisted (AA)CVD from a solution of zinc acetate and urea in methanol, with the carbodiimide ion being formed from the decomposition of the urea molecule. Thin film synthesis is achieved over a deposition temperature range 375 − 500 °C, with a minimum ratio of urea to zinc acetate of 2:1 and a maximum of 5:1 established as viable for film formation. This work presents the first example of the synthesis of a ZnNCN thin film, or indeed any metal carbodiimide thin film, using a CVD technique. Abstract : The concerted aerosol‐assisted CVD reaction of urea and zinc acetate in methanol enables the formation of zinc carbodiimide thin films. This can be achieved over a substrate temperature range of 375 to 500 °C with a minimum excess of 2 mol eq. of urea needed for pure ZnNCN, and an excess of up to 5 mol eq. tested.